The Transfer of Use of High Heirloom Property in Solok District in Maqashid Al-Syariah Review - Ramadhani, Ramadhani; Refliandi , Irvan; B, Syafriadi (Yayasan Lembaga Studi Makwa, 2023)
The transfer of the utilization of high inheritance assets in Nagari Muara Panas, Bukit Sundi District, Solok Regency often reaps pros and cons, because basically, high inheritance assets may not be sold or pawned except for four reasons, but the facts often show that high inheritance assets are used for the benefit of personal. This is what causes divisions among the people because of the transition from the utilization of the high inheritance property. The purpose of this study was to analyze the Maqashid al-Shariah review of the transfer of utilization of high inheritance assets in Nagari Muara Panas, Solok Regency. This type of research is field research. Data collection techniques in this study were carried out through interviews and documentation. The results of this study indicate that the form of diversion of the use of high heirlooms that occurred in Nagari Muara Panas, Bukit Sundi District, Solok Regency was carried out by pawning and trading by owners of high heirlooms for reasons of personal gain. Furthermore, Maqashid al-Shariah's review of the transfer of utilization of high inheritance assets in Nagari Muara Panas is permissible in order to preserve the soul in the form of medical treatment and preserve the mind in the form of educational expenses, all of which can be categorized at the dharuriyyat level. and this is at the level of tahsiniyyat.